Altering the concentration of silica tunes the functional properties of collagen–silica composite scaffolds to suit various clinical requirements. (December 2015) - Perumal, Sathiamurthi; Ramadass, Satiesh kumar; Gopinath, Arun; Madhan, Balaraman; Shanmugam, Ganesh; Rajadas, Jayakumar; Mandal, Asit Baran
Abstract: The success of a tissue engineering scaffold depends on a fine balance being achieved between the physicochemical and biological properties. This study attempts to understand the influence of silica concentration on the functional properties of collagen–silica (CS) composite scaffolds for soft tissue engineering applications. Increasing the ratio of silica to collagen (0.25, 0.5, 0.75, 1.0, 1.25, 1.5 and 2.0 w/w) gave a marked advantage in terms of improving the water uptake and compressive modulus of the CS scaffolds, while also enhancing the biological stability and the turnover time. With increase in silica concentration the water uptake and compressive modulus increased concurrently, whereas it was not so for surface porous architecture and biocompatibility which are crucial for cell adhesion and infiltration. Silica:collagen ratio of ≤1 exhibits favourable surface biocompatibility, and any further increase in silica concentration has a detrimental effect. Graphical abstract: Highlights: Influence of silica concentration on the functional properties of collagen-silica composites Compressibility and biological stability linearly increases with concentration of silica Silica concentration is crucial in favouring surface biocompatibility for cell adhesion. Tailor made properties by varying silica concentration according to the clinical requirements